PENGARUH KOMPETENSI, INDEPENDENSI, DUE PROFESSIONAL CARE, DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT (Survey pada Kantor Akuntan Publik Korwil Sumatera Bagian Tengah) - Anugerah, Rita; A, Al-azhar; ', Suryanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to analyze and gets empirical prove of the influence of competency, independency, due professional care and auditor ethic to the audit quality in the Public Auditor at Center Sumatera Estate. Competency measured by three dimensions, namely motivation, and social obligations. Independency are measured by three indicators, which is integrity having objectivity, having sincerity, and don’t compromise quality. Meanwhile professional ethic is measured with five dimensions which is integrity, objectivity, professional’s interest & accuracy, secrecy, and professional’s behavior.This research is a quantitative model using multiple linear regression to determine the effect af each independent and dependent variables. The population of this research is all of functional auditor in the financial Checkered Institute Delegation of Riau Province. The sample that is taken are all population which is as much 55 respondents with data taking via questionnaire’s broadcast.This research outcome represent that partially auditor competency and independency are not impact to the audit quality of Financial Checkered Institute Delegation of Riau Province. Meanwhile, the professional ethic is positive impact to the audit quality Financial Checkered Institute Delegation of Riau Province. In the meantime, the observational result simultan represent that all independent variable which is auditor accountability, independency, and professional ethic are impact to the audit quality of Financial Checkered Institute Delegation of Riau Province.Keyword: auditor competency, independency, due professional care, ethic and audit quality.